Leapfrogging the Clouds: Singapore Airlines' Innovative Transformation and Voyage to the Future - Chen, Weiheng (International Journal of Global Economics and Management, 2024)
This paper explores Singapore Airlines (SIA) strategic response to the COVID-19 pandemic, focusing on the airline's recovery strategy, digital transformation, and innovation initiatives. Despite facing significant challenges, SIA demonstrated resilience and adaptability through the application of Kotter's and Lewin's change models and a commitment to change. Quantitative data analysis indicates a notable recovery in SIA's financial performance, highlighting the company's dedication to innovation and operational excellence. The study concludes that SIA's approach underscores the significance of visionary leadership and proactive management in overcoming adversity and serves as a guide for sustainable growth in the aviation industry post-pandemic.